230POlaparib maintenance therapy in patients (pts) with a BRCA1 and/or BRCA2 mutation (BRCAm) and newly diagnosed advanced ovarian cancer (OC): SOLO1 China cohort. (24th November 2019) - Wu, L; Zhu, J; Yin, R; Wu, X; Lou, G; Wang, J; Gao, Y; Kong, B; Lu, X; Zhou, Q; Wang, Y; Chen, Y; et al.
Abstract: Background: SOLO1 (NCT01844986) is a randomized, double-blind, phase III trial evaluating the efficacy and safety of the PARP inhibitor, olaparib, as maintenance monotherapy in newly diagnosed advanced OC pts with a BRCAm. A separate pt cohort evaluated the efficacy and safety of olaparib in Chinese pts in this setting. Methods: The China cohort of SOLO1 planned to enrol ∼53 newly diagnosed OC pts who had completed first-line platinum-based chemotherapy and were in clinical complete or partial response. This sample size provided around a 90% chance to observe a hazard ratio (HR) of < 1, assuming a true HR of 0.62. Pts were randomized 2:1 to olaparib (300 mg bid; tablet) vs placebo. The primary endpoint was investigator-assessed progression-free survival (PFS; modified RECIST v1.1). Sensitivity analysis of PFS was performed by blinded independent central review (BICR). Results: All 64 randomized pts received study treatment (olaparib, n = 44; placebo n = 20). Median follow-up was ∼30 months in both arms. Median PFS was not reached in the olaparib arm and was 9.3 months in the placebo arm (Table). The most common AEs in the olaparib group were nausea (n = 28, 63.6%), anaemia (n = 25, 56.8%) and vomiting (n = 18, 40.9%). Grade ≥3 AEs occurred in 56.8% of olaparib pts vs 30.0% of placebo pts; the most common grade ≥3 AE was anaemia (n = 16, 36.4%). Olaparib dose interruptions, reductions and discontinuations occurred in 56.8%, 27.3% and 6.8% of pts, respectively (vs 30.0%, 10% and 0% of pts in the placebo arm). Conclusions: In the China cohort of SOLO1, a clinically relevant improvement in investigator-assessed PFS was observed in newly diagnosed OC pts receiving olaparib maintenance therapy. Olaparib treatment led to a 54% reduction in risk of progression or death vs placebo. The safety results were consistent with the known profile of olaparib in Chinese pts. Clinical trial identification: NCT01844986, release date 19 February 2016. Editorial acknowledgement: Medical writing assistance was provided by Laura Smart, MChem, from Mudskipper Business Ltd, funded by AstraZeneca and Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (MSD). Legal entity responsible for the study: AstraZeneca. Funding: AstraZeneca. Disclosure: J. Liu: Research grant / Funding (institution): AstraZeneca. X. Ma: Full / Part-time employment: AstraZeneca. J. Zhang: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. All other authors have declared no conflicts of interest.